Worldwide and regional prevalence rates of co-occurrence of insomnia and insomnia symptoms with obstructive sleep apnea: A systematic review and meta-analysis. (June 2019) - Zhang, Ye; Ren, Rong; Lei, Fei; Zhou, Junying; Zhang, Jihui; Wing, Yun-Kwok; Sanford, Larry D.; Tang, Xiangdong
Summary: Recent investigations have established that patients with obstructive sleep apnea (OSA) and insomnia have greater daytime impairments and reduced quality of life compared to those with either disorder alone. The present study reviewed current data on the co-occurrence prevalence of insomnia and insomnia symptoms with OSA and assessed its worldwide and regional prevalence based on World Health Organization (WHO) regions. A total of 37 studies were included in the analysis. The overall prevalence rates of insomnia, any insomnia complaints, difficulty falling asleep (DFA), difficulty maintaining sleep (DMS) and early morning awakening (EMA) found in OSA patients were 38%, 36%, 18%, 42%, and 21%, respectively. According to the regional classification of the WHO, the rates of DFA, DMS and EMA in OSA patients in the Western Pacific Region were lower than those in the European Region and the Region of the Americas. We also analyzed the pooled prevalence rates of OSA based on different apnea-hypopnea index (AHI) criteria in insomnia patients. The rates were 35% (AHI≥5) and 29% (AHI≥15), respectively. Regional differences of DFA, DMS and EMA in OSA patients may be related to sex, age and body mass index.